2019
DOI: 10.1016/j.jbusres.2019.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to donate: Exploring the role of religiousness in charitable donations

Abstract: This research investigates motivations to donate to charity among Muslims living in the UK. The research conducts in-depth interviews and explores charitable causes which Muslims support while examining the extent to which Muslims integrate religion into charitable donation behavior. Participants support a range of charitable causes-both internationally and locally that allows them develop a sense of attachment and interdependence with others. Findings point to five ways in which religiousness manifests itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 37 publications
2
42
0
3
Order By: Relevance
“…This research proposed two additional variables for enhancement: knowledge and trust to attitude. The study has articulated existing studies such as those of Bagheri, Chitsazan & Ebrahimi (2019) and Jamal et al (2019), in which TPB was extended with other variables. It was found that knowledge had a positive and significant impact on attitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research proposed two additional variables for enhancement: knowledge and trust to attitude. The study has articulated existing studies such as those of Bagheri, Chitsazan & Ebrahimi (2019) and Jamal et al (2019), in which TPB was extended with other variables. It was found that knowledge had a positive and significant impact on attitude.…”
Section: Discussionmentioning
confidence: 99%
“…In the zakat payment context, when muzaki understand zakat knowledge, they tend to pay zakat using all the information they have obtained. Jamal, Yaccob, Bartikowski & Slater (2019) argue that a high level of understanding of Islamic teachings and principles inspires Muslims to donate and give to charity. Husin and Rahman (2016) also found that knowledge had a significant effect on the attitude to participate in takaful products.…”
Section: Knowledgementioning
confidence: 99%
“…At the same time, the faith may also discourage public displays of giving that might lead to some individuals downplaying their religious giving (Diop et al 2018). Therefore, Muslims across many cultures have established formal and informal practices to nurture the institution of charity within their local communities as well as broader international communities (Jamal et al 2019;Maarouf 2012). Of course, religious communities also extend beyond local communities, and Muslims, like other religious groups, debate whether it is best to support local needs both inside and outside their community or to support a global religious ingroup (umma).…”
Section: Identity Values Norms Teachings and Affiliationmentioning
confidence: 99%
“…The level of religiosity has an interdependence relationship with the development of Islamic Spirit. The higher the level of religiosity, the higher the spiritual system, which is manifested in the form of akhlakul karimah consistently (Jamal, Yaccob, Bartikowski, & Slater, 2019) since "every worship activity that is right will affect the upholding of morals and cleanliness of the soul" (Ridla, 1373 H).…”
Section: Introductionmentioning
confidence: 99%